The relationship of muscle strength and pain in subacromial impingement syndrome - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2011)
Objective: We evaluated the relationship between muscle strength and pain in subacromial impingement syndrome (SIS). Methods: 18 female, 2 male twenty patients (mean age 48.15 +/- 5.9 years; range 32 to 60 years) with Stage I and II SIS were enrolled in the study. Upper, middle and lower trapezius, serratus anterior, supraspinatus and anterior deltoid muscle strengths were assessed bilaterally by a hand-held dynamometer. Each muscle was assessed 3 times and the mean value of strength was calculated. Pain and functional results were assessed with visual analog scale (VAS), and Constant scores. Modified Constant score was calculated, with the exclusion of pain parameters. Results: Middle trapezius, serratus anterior, supraspinaais and anterior deltoid muscle strengths of the shoulder with positive impingement signs were significantly lower than healthy opposite side (p=0.01, p=0.04, p=0.01, p=0.003). The mean Constant score was 57.46 and the mean VAS 6.85, in shoulders with SIS. There was a significant correlation between VAS and Constant score, without pain assessment (p=0.016, rs=-0.44). Conclusion: In this study we found a relationship between the middle trapezius, serratus anterior, supraspinatus and anterior deltoid muscle weaknesses and pain in SIS. This result indicates that these muscles should be evaluated and strengthened in required cases during the rehabilitation.
Keywords: Hand-held dynamometer; muscle strength; subacromial impingement syndrome; QUALITY-OF-LIFE; SHOULDER IMPINGEMENT; RECRUITMENT PATTERNS; ROTATOR STRENGTH; SYMPTOMS; RELIABILITY; PROTRACTION; RETRACTION; EXERCISES; IMPACT